Lung fibroblasts accelerate wound closure in human alveolar epithelial cells through hepatocyte growth factor/c-Met signaling - Ito, Yoko; Correll, Kelly; Schiel, John A.; Finigan, Jay H.; Prekeris, Rytis; Mason, Robert J. (American journal of physiology. Lung cellular and molecular physiology, 2014)
There are 190,600 cases of acute lung injury/acute respiratory distress syndrome (ALI/ARDS) each year in the United States, and the incidence and mortality of ALI/ARDS increase dramatically with age. Patients with ALI/ARDS have alveolar epithelial injury, which may be worsened by high-pressure mechanical ventilation. Alveolar type II (ATII) cells are the progenitor cells for the alveolar epithelium and are required to reestablish the alveolar epithelium during the recovery process from ALI/ARDS. Lung fibroblasts (FBs) migrate and proliferate early after lung injury and likely are an important source of growth factors for epithelial repair. However, how lung FBs affect epithelial wound healing in the human adult lung has not been investigated in detail. Hepatocyte growth factor (HGF) is known to be released mainly from FBs and to stimulate both migration and proliferation of primary rat ATII cells. HGF is also increased in lung tissue, bronchoalveolar lavage fluid, and serum in patients with ALI/ARDS. Therefore, we hypothesized that HGF secreted by FBs would enhance wound closure in alveolar epithelial cells (AECs). Wound closure was measured using a scratch wound-healing assay in primary human AEC monolayers and in a coculture system with FBs. We found that wound closure was accelerated by FBs mainly through HGF/c-Met signaling. HGF also restored impaired wound healing in AECs from the elderly subjects and after exposure to cyclic stretch. We conclude that HGF is the critical factor released from FBs to close wounds in human AEC monolayers and suggest that HGF is a potential strategy for hastening alveolar repair in patients with ALI/ARDS.